2020
DOI: 10.1111/ane.13366
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory protein signatures in cryptogenic and large artery atherosclerosis stroke

Abstract: Objectives The cause of ischemic stroke remains unknown, cryptogenic, in 25% of young and middle‐aged patients. We hypothesized that if atherosclerosis is prominent in cryptogenic stroke, it would have a similar proinflammatory protein signature as large artery atherosclerosis (LAA) stroke. Materials & Methods Blood was collected in the acute phase and after 3 months from cryptogenic (n = 162) and LAA (n = 73) stroke patients aged 18–69 years and once from age‐matched controls (n = 235). Cryptogenic stroke was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…Interestingly, blood CRP levels differ between stroke subtypes, since large‐vessel strokes had higher CRP levels at follow‐up compared with all other stroke subtypes, including small‐vessel strokes, cardioembolic strokes, cryptogenic strokes, and others (Ladenvall et al , 2006). More recent findings also reported a higher frequency of activated human leukocyte antigen (HLA − DR + ) cells in blood 2 months after ischemic stroke (Roth et al , 2018), and found that circulating IL‐4 and IFN‐γ levels persisted elevated up to 3 months poststroke, regardless of stroke etiology (Holmegaard et al , 2021). Hence, whether post‐stroke chronic inflammation could be influenced by the infarct topography and/or the co‐existence of any other comorbidity still needs to be elucidated.…”
Section: Introductionmentioning
confidence: 96%
“…Interestingly, blood CRP levels differ between stroke subtypes, since large‐vessel strokes had higher CRP levels at follow‐up compared with all other stroke subtypes, including small‐vessel strokes, cardioembolic strokes, cryptogenic strokes, and others (Ladenvall et al , 2006). More recent findings also reported a higher frequency of activated human leukocyte antigen (HLA − DR + ) cells in blood 2 months after ischemic stroke (Roth et al , 2018), and found that circulating IL‐4 and IFN‐γ levels persisted elevated up to 3 months poststroke, regardless of stroke etiology (Holmegaard et al , 2021). Hence, whether post‐stroke chronic inflammation could be influenced by the infarct topography and/or the co‐existence of any other comorbidity still needs to be elucidated.…”
Section: Introductionmentioning
confidence: 96%
“…1,6,7 It follows that inflammation has previously been implicated in the main etiological subtypes of ischemic stroke: large artery atherosclerosis (LAA), cardioembolic stroke, small artery occlusion stroke (SAO), and cryptogenic stroke. 1,8,9 Moreover, vessel wall inflammation has been proposed as one of the causes of cervical arterial dissection (CeAD). 10 Although inflammation appears to be relevant for different ischemic stroke subtypes, few studies on circulating inflammatory plasma proteins have performed subtype-specific analyses.…”
mentioning
confidence: 99%
“…It plays an important role in the pathogenesis of IS due to its ability to cross the blood–brain barrier 36 . The level of eotaxin increases with the occurrence of IS, and the increase in eotaxin aggravates IS injury 37 . Macrophage inflammatory protein‐1 gamma (MIP‐1γ) also belongs to the CC‐chemokine family.…”
Section: Discussionmentioning
confidence: 99%